Language Preferences of Bilingual/Multilingual African International Students - Tekin, Nazik Müge; Topal, Erol (Kastamonu Egitim Dergisi, 2025)
Purpose: The aim of this study is to determine the language preferences of African bilingual/multilingual university students in their sociocultural, daily, and religious lives. Additionally, the study will determine the effect of demographic characteristics (country, gender, and religion) of African bi/multilingual students participating in the study on their language preferences in the specified areas and reveal the similarities and differences in these preferences based on demographic factors with their reasons. Design/Methodology/Approach: The “correlational survey model” was used to examine the relationship between the variables of the language preferences of African bilingual/multilingual students in different areas. The study sample was 31 international students randomly selected from bilingual/multilingual African students studying at Kastamonu University. First, demographic information of the participants was obtained with the forms prepared for data collection; then, 45 visuals related to sociocultural life, daily life, and religious life were presented to the participants and it was determined in which language they conceptualized the visual. Basic statistical techniques were employed to analyze the data, and the relationship between demographic characteristics and language preferences was tabulated. Findings: The findings indicate that the language preferences of African bilingual and multilingual students are significantly influenced by their historical backgrounds, cultural identities, and sociopolitical environments. It was concluded that French, English, and Portuguese are the dominant languages in sociocultural and daily contexts. Both genders prefer global languages in sociocultural settings but have differing preferences in daily life. Among Muslim participants, Arabic is preferred, while Christian participants tend to favor Turkish for Islamic terms. Local languages are less preferred overall based on country and gender but are more commonly chosen for religious word choices. Highlights: The analysis concluded that global languages, notably French and English, exhibit significant dominance in sociocultural interactions and everyday communication. In contrast, Arabic holds a prominent position primarily within religious contexts. Furthermore, it was apparent that local languages are utilized relatively infrequently. Turkish was predominantly favored in both religious and sociocultural contexts. Notable variations in language preferences are observed based on gender and religious affiliations. It was observed that female participants presented a broader language profile.